Bioelectrochemical energy storage in a Microbial Redox Flow Cell - Márcia Santos (2021)
Bioelectrochemical systems (BESs) can be used to transform the electrochemical energy of fuels in electricity in Microbial Fuel Cells (MFC). However, this generated bioenergy can be captured by external loads or dissipated as heat, instead of being utilized or stored. A Microbial Redox Flow Cell (MRFC) is here presented, which demonstrates the integration of a BESs with a Redox Flow Cell (RFC); it is an innovative approach to store the energy released by the electroactive bacteria into storable electrochemical energy (electrochemical fuels) easily and efficiently convertible into electricity. The MRFC uses Geobacter sulfurreducens as biocatalyst: (i) operating as Exoelectrogenic Bacteria for the reduction of the redox pair anthraquinone-2,6-disulfonate (2,6-AQDS) in anthrahydroquinone-2,6-disulfonate (2,6-AQDSH2) (BESs as bioanode of MRFC) and (ii) operating as Electrotrophic Bacteria for oxidation of the redox pair ferrocyanide ([Fe(CN)6]4−) to ferricyanide ([Fe(CN)6]3−) (BESs as biocathode of MRFC). In the reduction of 2,6-AQDS, current density of 0.048 mA cm−2 was recorded with a bioconversion to 2,6-AQDSH2 of ca. 27%. As for the oxidation of [Fe(CN)6]4−, 35.7% was oxidized to [Fe(CN)6]3−. The bio-converted electrochemical fuels were introduced in a RFC, 2,6-AQDSH2 as negalyte and ferricyanide ([Fe(CN)6]3−) as posilyte. An MRFC, operating with 29 cycles reached Coulombic efficiencies of ca. 99% and Energy efficiencies of ca. 55%. The concept of a MRFC is successfully demonstrated.